Effect of pumpkin (Cucurbita maxima) seed meal as a supplementing diet to free-ranging goats on growth performance and semen quality - Maselema, D.; Chigwa, F.; Chingala, G. (2021)
Range forages consumed by free-range goats are commonly deficient in protein, energy and minerals resulting in low productivity of the goats. The main objective of this study was to evaluate the effect of whole pumpkin seed meal supplementing diet on growth performance and semen quality of free-range goats. Thirty Malawian local bucks with an initial weight of 12.4±0.3 kg and age of 6 months were studied in completely randomised design. The treatments were: free-grazing with either supplementing diet of pumpkin seed meal or soybean meal and grazing only. The supplementing diets were mixed with maize bran to make them comparable. The supplementing diets were offered to goats (500 g each goat) before grazing (7:00 am) in individual pens followed by free graze for 7h. The experiment ran for 150 days. The measurements included: feed and refusals of the supplementing diet, live body weight, scrotal circumference and semen quality characteristics. The intake of supplementing diets was high in bucks consuming soybean supplementing diet than pumpkin seed meal supplementing diet (P = 0.0489). Bucks supplemented with either soybean or pumpkin seed meal had higher final weight and average daily gain (P < 0.05) than the non-supplemented goats. However, the final live body weight and average daily gain did not differ (P = 0.639) between goats on soybean and pumpkin seed meal supplementing diets. The bucks supplemented with pumpkin seed meal had the widest scrotal circumference (P < 0.05) of all the treatments studied. The bucks fed a supplementing diet containing pumpkin seed meal had higher semen pH (P < 0.05) than bucks on sole grazing group and soybean supplementing diet. Bucks on pumpkin seed supplementing diet had the greatest scores (P < 0.05) on total sperm motility and progressive motility; and sperm concentration followed by the bucks on soybean and the bucks on grazing only had the lowest score. The whole pumpkin seed meal could be used to improve productive performance and semen quality characteristics of free-ranging bucks.